Spousal support during pregnancy in the Nigerian rural context: a mixed methods study - O. Arisukwu (BMC, 2021)
Abstract Background Pregnancy constitutes a global health concern, thus the need for spousal support during this period cannot be overemphasized. This study examined the kinds of support pregnant women expected and received from their spouses as well as the effect of such supports during pregnancy, labour, and delivery. Methods The study adopted both quantitative and qualitative methods of data collection. The respondents were selected using multistage and simple random sampling techniques. Results Findings showed that respondents expected and received maximum support from their spouses during pregnancy, labour, and delivery. Spiritual support such as praying and fasting was top of the kinds of support pregnant women expected and received from their husbands during pregnancy and delivery. Others include helping in house chores, financial provision, taking care of other children, accompanying to labour room, and sexual support. More than three-quarters of the respondents stated that maximum support from their husbands made pregnancy, labour, and delivery easier. Cramer’s V showed that the association between support and husbands’ occupation was 0.233 and Pearson Chi-square showed that the association was statistically significant χ2(2) = 27.894,p < .001. Conclusion The study concluded that spousal support during pregnancy was high among rural women in Southwestern Nigeria, and it impacted positively on their wife’s period of pregnancy, labour, and delivery. A high level of spousal support should be sustained to promote family bonding and development as well as reduce maternal and child mortality.